Historical Virtualization: Analog and Digital Concerns in the Recreation, Modeling and Preservation of Contemporary Piano Repertoire. - NANOU, CHRYSI; HAMILTON, ROB (Leonardo Music Journal, 2017)
Modern efforts to preserve and reinterpret canonic musical works in the contemporary piano repertoire often take advantage of new technologies, fundamentally changing core aspects of the works themselves. By approaching preservation as a form of virtualization-in this case the creation of a functional interpretative model of each musical work-artists and researchers can create robust and performable digital versions of important musical systems. This paper introduces the idea of virtualization as a compositional modeling technique and offers three case studies in which digital versions of contemporary piano repertoire were designed and developed.